Effect of Heat Stress on Concentrations of Faecal Cortisol Metabolites in Dairy Cows. Issue 3 (19th April 2016) - Rees, A; Fischer‐Tenhagen, C; Heuwieser, W
Contents: The negative impact of heat stress on health and productivity of dairy cows is well known. Heat stress can be quantified with the temperature–humidity index (THI) and is defined as a THI ≥ 72. Additionally, animal welfare is affected in cows living under heat stress conditions. Finding a way to quantify heat stress in dairy cows has been of increasing interest over the past decades. Therefore, the objective of this study was to evaluate concentrations of faecal glucocorticoid metabolites [i.e. 11, 17‐dioxoandrostanes (11, 17‐DOA)] as an indirect stress parameter in dairy cows without heat stress (DOA 0), with heat stress on a single day (acute heat stress, DOA 1) or with more than a single day of heat stress (chronic heat stress, DOA 2). Cows were housed in five farms under moderate European climates. Two statistical approaches (approach 1 and approach 2) were assessed. Using approach 1, concentrations of faecal 11, 17‐DOA were compared among DOA 0, DOA 1 and DOA 2 samples regardless of their origin (i.e. cow, unpaired comparison with a one‐wayanova ). Using approach 2, a cow was considered as its own control; that is 11, 17‐DOA was treated as a cow‐specific factor and only paired samples were included in the analysis for this approach (paired comparison with t ‐tests). In approach 1 (p   =   0.006) and approach 2 (p   =   0.038), 11, 17‐DOA values of cows under acute heat stress were higher compared to those of cows without heat stress. Our results also indicate that acute heat stress has to be considered as a confounder in studies measuring faecal glucocorticoid metabolites in cows to evaluate other stressful situations.